Effect of farmyard manure on Biomass yield, carbon assimilation Potential and correlation coefficient in fodder maize (Zea mays l.) in different agro climatic Zones - B. Rajesh Kumar; Thanga. Thamil Vanan; T. Sivakumar; K.N. Selvakumar; V.M. Sankaran; S. Saraswathi (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A field experiment was conducted to study the effect of inorganic fertilizer and the synergistic effect of farmyard manure (organic) with inorganic fertilizer on the Green Fodder Yield (GFY), Dry Matter Yield (DMY), Carbon Assimilation Potential (CAP) and Correlation Coefficient between soil organic carbon and plant organic carbon in Fodder Maize (Zea mays L.) crop field in North Eastern and Western Zones of Tamil Nadu, India during summer season of 2012. For this study, in Western zone two districts viz., Coimbatore and Erode districts and in North Eastern Zone Tiruvannamalai and Vellore districts were selected for the field experiments. From the selected district, two villages were randomly selected (2 village/ district) for field experiments totaling to eight experimental sites for the study. Green fodder yield for T1 (Recommended dose of NPK) and T2 (Recommended dose of organic and inorganic fertilizer) on 60 day ranged between 36.15 to 39.07 t/ha and 36.92 to 40.23 t/ha for all villages. On the other hand, Dry Matter Yield for T1 and T2 on 60th day varied between 6.37 to 6.91 t/ha and 6.51 to 7.09 t/ha for all villages. Carbon Assimilation Potential for T1, T2 on 60 day varied between 3.17 to 3.82 t/ha and 3.32 to 3.99 t/ha for all villages. A positive correlation (P<0.01) existed between soil and plant organic carbon in Fodder Maize for both treatments (T1 and T2) during the study period. This study recommended the use of farmyard manure along with inorganic fertilizer as the best option for increased biomass yield which also had positive effect on carbon sequestration potential.